Improving spelling for at‐risk kindergartners through element skill frequency building. (30th December 2019) - Kostewicz, Douglas E.; Kubina, Richard M.; Brennan, Kaitlyn M.
Abstract: A student's ability to spell affects literacy outcomes. Students profit from explicit spelling instruction but may also benefit from frequency building or systematic practice. The method of frequency building leads toward effortless performance or behavioral fluency. Reaching certain frequencies of behavior produces a critical learning outcome called application. The current study focused on the effects of building element spelling behaviors for at‐risk kindergartners and the subsequent application to a compound spelling skill. Visual and quantitative analysis suggest a clear experimental effect between the attainment of performance criterion for letter sounds, letter naming, and sequencing on students' spelling behavior. A discussion of the results precedes future research directions.